THE IMPLEMENTATION OF GOOGLE CLASSROOM IN IMPROVING STUDENTS’ READING COMPREHENSION AT MAN 4 JAKARTA - Dewi, Nurmala -; Zahrowi, Eva; Sulistyawati, Meiva Eka Sri (Lingual Journal of Language and Culture; Vol 9 No 1 (2020): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2020.v09.i01.p04, 2020)
The objectives of this study were to investigate the use of Google Classroom in improving reading comprehension, how students’ perceptions when engaging with Google Classroom in the learning process, and what obstacles encountered in implementing it. The methodology applied in this study is mixed-method, including both quantitative and qualitative methods which are conducted among 27 students on grade XI of Madrasah Aliyah Negeri (MAN) 4 Jakarta. While the data was collected by reading comprehension tests, interviewing students, and filling the questionnaire to gain their perceptions about Google Classroom. The result showed that using Google classroom could improve students’ scores on reading comprehension; this indicated by comparing pre-test and post-test. Regarding students’ perceptions of using Google Classroom, it revealed that some students still preferred to study in the classroom since they could interact directly and easily with the teacher. Contrary, some of them would choose learning by Google Classroom because it is more interesting and easier to access whenever and whatever they are. The obstacles were encountered in the learning processes are such as unstable internet connection in the school and unskilled teachers to operate the application.  Therefore, using technology has to consider the devices and sophisticated equipment to support a better system in the learning process. Besides, the humans to operate the system should be trained well in order for the learning process is going smoothly.